2019
DOI: 10.15244/pjoes/90357
|View full text |Cite
|
Sign up to set email alerts
|

Soil Contamination with Copper and its Effect on Selected Soil Properties After Applying Neutralizing Substances

Abstract: The aim of this study was to determine the effects of copper contamination (0, 50, 100, 150, and 200 mg Cu/kg of soil) and neutralising substances on the content of total organic carbon, total nitrogen, available forms of phosphorus, potassium, and magnesium, and C:N ratio in soil. The experiment was conducted in four series: without neutralising substances and with compost 3% of soil weight, bentonite 2% of soil weight, and zeolite 2% of soil weight. Contamination of soil with copper and the application of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…This may be due to the fact that it is an essential micronutrient in the soil. According to Chrysargyris et al (2019), Cu is among the essential micronutrients though its availability in excessive levels may be harmful to the plants (Wyszkowski, 2019). The concentration of heavy metals in all transects were below the WHO and TZS maximum permissible limits in soils.…”
Section: Discussionmentioning
confidence: 89%
“…This may be due to the fact that it is an essential micronutrient in the soil. According to Chrysargyris et al (2019), Cu is among the essential micronutrients though its availability in excessive levels may be harmful to the plants (Wyszkowski, 2019). The concentration of heavy metals in all transects were below the WHO and TZS maximum permissible limits in soils.…”
Section: Discussionmentioning
confidence: 89%
“…Wyszkowski [115] studied the reduction of the effect of Cu contamination on the content of the total organic carbon, total nitrogen, magnesium, potassium, and the available form of phosphorus by adding organic compounds, bentonite or zeolite (2%). Considering that Cu pollution increases the total nitrogen content, the potassium amount, and the available phosphorus, thus negatively affecting the soil properties, the results indicated that amendment with zeolites decreased the content of the total nitrogen (48%), and reduced the amount of potassium, organic carbon, and available phosphorus by 11%-12%.…”
Section: Natural Zeolites and Soil Pollutionmentioning
confidence: 99%
“…Heavy metals accumulate in the food chain and may become toxic to humans. Therefore, the study of the content of macro-and trace elements, heavy metals in soil has long attracted both foreign and domestic scientists (Sola, 2003;Chibuike, 2014;Gil, 2004;Redondo-Gómez, 2009;Wyszkowski, 2017Wyszkowski, ,2019Shitova, 2005;Bakayeva, 2016;Stepanova, 2012;Firago, 2012). Most studies of deposit environments are carried out in urbanized areas with high technogenic load (Firago, 2012;Shitov, 2005), on domestic refuse landfill soils (Sola, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the purpose of this study is to determine the content of certain trace elements and heavy metals in soil, rhubarb, and its processed product -kvass made in different ways. Similar studies to determine the level of toxic elements in veterinary supervision objects are being conducted in China, Poland, America and in many regions of Russia (Chibuike, 2014;Gil, 2004;Redondo-Gómez, 2009;Wyszkowski, 2017Wyszkowski, ,2019. Lead (Pb) and Cadmium (Cd) concentrations in soils of four Ibadan landfill sites and a control site were determined in Nigeria.…”
Section: Introductionmentioning
confidence: 99%